2020
DOI: 10.1038/s41598-020-66062-1
|View full text |Cite
|
Sign up to set email alerts
|

The value of circulating microRNAs for early diagnosis of B-cell lymphoma: A case-control study on historical samples

Abstract: MicroRNAs are small regulatory RNAs that are deregulated in a wide variety of human cancers, including different types of B-cell lymphoma. Nevertheless, the feasibility of circulating microRNA for early diagnosis of B-cell lymphoma has not been established. To address the possibility of detecting specific circulating microRNAs years before a B-cell lymphoma is diagnosed, we studied the plasma expression of microRNA first in pre-treatment samples from patients with diffuse large B-cell lymphoma and subsequently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…One group of researchers correlated serum levels of miR-224, miR-455-3p, miR-1236, miR-33a and miR-520d-3p with responses to classic chemotherapy [ 133 ]. More recently, one study analyzed the plasma repository samples of 16 blood donors taken months or years before the diagnosis of DLBCL [ 134 ]. They observed upregulated microRNAs at the time of diagnosis, namely miR-328, miR-21-5p, miR-326 and miR-199a-5p.…”
Section: Advances In Molecular Methods and New Perspectives In Clinical Practicementioning
confidence: 99%
See 1 more Smart Citation
“…One group of researchers correlated serum levels of miR-224, miR-455-3p, miR-1236, miR-33a and miR-520d-3p with responses to classic chemotherapy [ 133 ]. More recently, one study analyzed the plasma repository samples of 16 blood donors taken months or years before the diagnosis of DLBCL [ 134 ]. They observed upregulated microRNAs at the time of diagnosis, namely miR-328, miR-21-5p, miR-326 and miR-199a-5p.…”
Section: Advances In Molecular Methods and New Perspectives In Clinical Practicementioning
confidence: 99%
“…They observed upregulated microRNAs at the time of diagnosis, namely miR-328, miR-21-5p, miR-326 and miR-199a-5p. Interestingly miR-326 and miR-199a-5p were also upregulated in the last sample before diagnosis, indicating that these miRNAs were already upregulated in the absence of symptoms or diagnosis [ 134 ]. Similarly, miR-375 was found to be most down-regulated in DLBCL patients.…”
Section: Advances In Molecular Methods and New Perspectives In Clinical Practicementioning
confidence: 99%
“…MiR-145 and miR-375 were lower in two studies and are considered tumor suppressors in different cancer types. MiR-145 targets among others the oncogenes MYC and protein C-ets-1 (ETS1), and miR-375 targets the astrocyte elevated gene 1 (AEG-1), yes-associated protein 1 (YAP1), insulin like growth factor 1 (IGF1R) and pyruvate dehydrogenase kinase isoenzyme 1 (PDK1) [58,63,[66][67][68]. MiR-15a was higher in three different studies [55,64,69].…”
Section: Micrornamentioning
confidence: 99%
“…MiR-155 is generally known as an oncomiR in many different tumors, targeting genes that play a central role in lymphomagenesis, such as suppressor of cytokine signaling (SOCS), phosphatidylinositol 3-kinase regulatory subunit alpha (PIK3R1) and src homology 2-domain-containing inositol 5′-phosphatase 1 (SHIP1) [ specimens [77]. Interestingly, dysregulation of cell-free miRNAs may precede the diagnosis up to 2 years, highlighting their potential as early biomarkers, before the onset of clinical symptoms [66]. For DLBCL subclassification, no miRNA was found to be significantly dysregulated in at least two different studies.…”
Section: Micrornamentioning
confidence: 99%
“…Subsequently, they validated the identified miRNA signature in a confirmatory cohort comprising samples from blood donors, who later developed different types of B-cell lymphoma to test pre-diagnostic plasma samples for early diagnosis. In the end, they verified that both miR-326 and miR199a-5p were upregulated months to years before diagnosis, which showed that changes in plasma miRNAs may precede the development of symptoms of NHL [ 126 ].…”
Section: Mirnas and Lncrnas As Potential Biomarkers For Nhlmentioning
confidence: 99%